Benjamin and Koolhaas: History's Afterlife - Frances Hsu (Footprint)
Dialectical images are at the core of the methods suggested by two books written four decades apart yet published around the same time. The Arcades Project (first published as Das Passagen-Werk in 1981) and Delirious New York (1978) use images to critique established modes of historical interpretation. Each proposes a methodology of historical speculation based on the interpretation of fragmentary visual phenomena. Both construct alternative historical narratives about the impact of technology, mass culture and economy on the city. This essay contrasts and compares the similarities and differences between the respective authors’ treatments of the nineteenth century arcade and the Manhattan skyscraper to examine how the strategies and definitions suggested by Benjamin and Koolhaas address the function of images as tools for critical architectural analysis and knowledge.